2007
DOI: 10.1016/j.jss.2006.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Claudin-1 Expression Correlates with Malignancy of Hepatocellular Carcinoma

Abstract: Attenuated expression of CL-1 closely correlates with the dedifferentiation and portal invasion of HCC. Down-regulated CL-1 expression may serve as a potential marker for a poor prognosis in HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 32 publications
4
58
0
Order By: Relevance
“…Attenuated expression of claudin-1 closely correlates with the dedifferentiation and portal invasion of hepatocellular carcinoma [35]. Defect in claudin-1 expression increases paracellular permeability in polarized hepatic cell lines, supporting the hypothesis that paracellular bile leakage through deficient TJs is involved in liver pathology observed in NISCH syndrome [28].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Attenuated expression of claudin-1 closely correlates with the dedifferentiation and portal invasion of hepatocellular carcinoma [35]. Defect in claudin-1 expression increases paracellular permeability in polarized hepatic cell lines, supporting the hypothesis that paracellular bile leakage through deficient TJs is involved in liver pathology observed in NISCH syndrome [28].…”
Section: Discussionmentioning
confidence: 59%
“…During cancer development, the expression of several TJ components usually decreases [27,28,35], however, elevated expression of TJ components have been detected in certain tumors [9,[36][37][38]. In contrast to hepatocellular carcinoma (HCC) [7,39], overexpression of claudin-4 has been observed in cholangiocarcinoma [29], in colon cancer [40], in pancreatic ductal carcinoma [41] and in several other malignancies [37,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Claudin-3 and claudin-4 have also been shown to be overexpressed in breast, gastric, ovarian and pancreatic cancers (10)(11)(12). In contrast, Higashi et al (1) reported reduced levels of claudin-1 in malignant hepatocellular carcinoma, and another researcher demonstrated that claudin down-regulation is associated with higher invasiveness (13). The results described above confirm not only that claudins are dysregulated in many types of cancer, but also that the nature of this dysregulation is highly specific according to cancer type.…”
Section: Modulation Of Egr-1 Expression As Well As Metastasis-involvementioning
confidence: 99%
“…Patients whose liver cancer has metastasized have poor prognoses and therefore novel prevention strategies are urgently required in order to save lives (1). In this study, we present a new paradigm for the prevention of liver cancer metastasis by using histone deacetylase (HDAC) inhibitors to induce early growth response gene-1 (Egr-1), a Cys2-His2-typed zinc-finger transcription factor, and the restoration of tight junctions (TJs) in liver cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in hepatocellular carcinoma, claudin-1 expression was reduced in poorly differentiated hepatocellular carcinomas. 63 The decrease in claudin-1 expression mediated by Src may be associated with dedifferentiation in colon cancer tumorigenesis. However, dedifferentiation cannot be primarily attributed to the claudin-1 decrease; claudin-1 overexpession in the colon cancer cell line SW480 actually resulted in dedifferentiation.…”
Section: Discussionmentioning
confidence: 99%